DEVELOPING A MODEL FOR ASSESSMENT IN PRIMARY SCHOOLS IN MASERU, LESOTHO - KHECHANE, NKOJA CLAUDIA (Bloemfontein: Central University of Technology, Free State, 2016)
The purpose of this research was to investigate primary mathematics teachers’ assessment practices in the context of the new integrated primary curriculum in Maseru, Lesotho, in an attempt to develop an assessment model applicable to their context. In an attempt to address this aim, teachers’ assessment practices and their understanding of assessment for learning (AfL) before and after AfL training were established. Furthermore, teachers’ classroom practices which reflect an understanding of AfL after training were explored. The research also examined the contextual tensions that exist for teachers when implementing AfL practices. The study was promoted by the fact that in the 1980s attempts were made in Lesotho to implement continuous assessment (CASS) but these were unsuccessful due to the lack of clarity of the concept among implementers and the contextual challenges experienced. Currently another policy on assessment, namely curriculum and assessment policy has been introduced in Lesotho primary schools and this research attempted to establish whether implementers were ready and clear about the innovation. The study adopted both positivist and interpretivist positions in which both quantitative and qualitative approach were employed. Data was collected using a survey, classroom observation and a semi-structured interview. The survey was conducted on 250 primary school teachers out of which eight mathematics teachers from four primary schools were trained on AfL issues. The training was conducted in two stages and teachers were later observed and interviewed. Findings from the survey revealed that teachers who participated in the study were not clear about AfL. However, after training, teachers were now clear about what AfL was all about though their classroom practices did not reflect much of that knowledge. There were some elements of AfL which teachers were able to implement and there were those which they could not. Teachers were able to communicate learning intentions and the success criteria at the beginning of the lessons. Learners were able use peer and self-assessments though informally as teachers did not provide them with the necessary tools for effective use. Learners also were able to use indicators correctly. However, findings showed that teachers were not providing descriptive feedback which showed learners’ strengths and weaknesses. Use of symbols instead of crosses and ticks did not make any difference in indicating the level of learners’ performance. The study revealed that there were some challenges which teachers encountered as they implemented AfL. These challenges were lack proper training and support, shortage of resources, high teacher-pupil ratio, teachers’ increased workload, reduced teaching time, lack of preparation time and lack of time to write performance statements. Generally, the training provided had positive impact on teachers’ assessment practices and their understanding of AfL. There were some assessment practices such as writing and sharing success criteria which teachers could not do before training but were able to do afterwards and their understanding of AfL had also improved. The researcher developed a model which will improve primary teachers’ implementation of AfL in mathematics. She also developed a model of teacher change for effective implementation of the assessment for learning policy.
Published Thesis
Keywords: Curriculum and Assessment Policy; New Integrated Primary Curriculum; Assessment; Assessment Practices; Learning Intention; Teachers’ Understanding; Primary Mathematics Teachers; Summative Assessment; Success Criteria; Formative Assessment; Assessment for Learning